Fourth International ACM Symposium on Field-Programmable Gate Arrays 1996
DOI: 10.1109/fpga.1996.242437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FPGA Resources for Built-In Self-Test of Programmable Logic Blocks

Abstract: We present a new approach for FPGA testing that exploits the reprogrammability of FPGAs to create Built-In Self-Test (BIST) logic only during off-line test. As a result, BIST is achieved without area or performance penalties to the system function implemented by the FPGA, since the FPGA is reconfigured for normal system operation. An analysis of Look-Up Table (LUT) based FGPA architectures yields a general expression for the number of test sessions and establishes the bounds on FPGA logic resources required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Testing before programming presents a wide spectrum of problems, for which a number of researchers have proposed innovative solutions. [3][4][5][6][7][8] Testing an FPGA chip poses a challenging problem for test engineers. It requires implementing various configurations (programmings) of the FPGA.…”
mentioning
confidence: 99%
“…Testing before programming presents a wide spectrum of problems, for which a number of researchers have proposed innovative solutions. [3][4][5][6][7][8] Testing an FPGA chip poses a challenging problem for test engineers. It requires implementing various configurations (programmings) of the FPGA.…”
mentioning
confidence: 99%
“…The approach of [3] utilizes a BET-based technique, in which the logic resources are configured as units under test, test generators and verifiers. [9] has presented a new approach for testing FPGAs by utilizing their programmable and reconfiguration capabilities.…”
Section: : Reviewmentioning
confidence: 99%
“…An area which only recently has been investigated, is testing and diagnosis. For logic resources, two approaches can be distinguished: the B E T (Built-In Self-Test)-based approach of [3] and the array-based approach of [4,9]. However, both these approaches are applicable t o FPGAs and to logic resource testing only; it has been reported that in a VLSI chip of this nature, the most likely place for a fault is the interconnect [6,10].…”
Section: : Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field Programmable Gate Arrays (FPGAs) combine the flexibility of mask programmable gate arrays with the convenience of field programmability [1][2][3][4][5][6][7][8][9][10][11][12]. There are many FPGA types but one very important is the static-RAM based FPGA architecture.…”
Section: Introductionmentioning
confidence: 99%